Dietary total antioxidant capacity and head and neck cancer: a large case-control study in Iran - Toorang, Fatemeh; Seyyedsalehi, Monireh Sadat; Sasanfar, Bahareh; Rashidian, Hamideh; Hadji, Maryam; Mohebbi, Elham; Safari, Roya; Najefi, Farid; Naghibzadeh-Tahami, Ahmad; Boffetta, Paolo; Zendehdel, Kazem (Frontiers in Nutrition, 2023)
Background Data on the association between head and neck cancer (HNC) and dietary factors are inconclusive. No study has so far investigated the association between dietary total antioxidant capacity (dTAC) and HNC concerning interactions with other risk factors. Method Pathologically confirmed new diagnosed HNC patients were included in this study. The control group was healthy hospital visitors who were frequently matched with patients on age (5 years interval), gender, and province of residence. Trained interviewers administered a validated Food Frequency Questionnaire (FFQ) to assess the participants’ food intake 1 year before the cancer diagnosis. Data on TAC scores of foods was collected by Ferric Reducing Antioxidant Power (FRAP) and Total Radical-trapping Antioxidant Parameters (TRAP) from published data. We applied logistic regression adjusted for age, sex, energy intake, socioeconomic status, province, opium use, alcohol use, physical activity, and dental health. We also studied the interaction of dTAC with tobacco smoking status, and opium use on the risk of HNC. Results We recruited 876 HNC patients and 3,409 healthy controls. We observed a significant decrease in the odds of HNC with increasing dTAC scores. The OR of HNC for the third vs. the first tertile was 0.49 (95%CI 0.39–0.61) for FRAP and 0.49 (95%CI 0.39–0.62) for TRAP. Both dTAC scores were inversely associated with lip and oral (T3 ver. T1 OR = 0.51; 95%CI 0.36–0.71 for FRAP and OR = 0.59; 95% CI 0.44–0.82 for TRAP) and larynx (T3 ver. T1 OR = 0.43; 95%CI 0.31–0.61 for FRAP and OR = 0.38; 95% CI 0.26–0.55 for TRAP) cancers. There was no interaction between tobacco smoking, opium use; and TRAP or FRAP on the risk of HNC. Conclusion An antioxidant-rich diet in terms of FRAP or TRAP could decrease the risk of HNC and its subtypes.